Manajemen Pembelajaran Anak Usia Dini - Haryono, Mimpira; Bendriyanti, Rita Prima; Rulismi, Dwi (Early Childhood Research and Practice, 2023)
This study aims to describe the management of early childhood learning at Putri Ayu Preschool in Bengkulu City, including planning, implementation, and evaluation. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that learning planning is carried out through the preparation of a Lesson Implementation Plan (RPP) in accordance with the applicable curriculum. Learning is active, enjoyable, and play-based, despite limited resources. Evaluation is conducted through authentic assessments involving observation, portfolios, and communication with parents. Overall, learning management at Putri Ayu Preschool is well-functioning, but still requires improvement, particularly in the use of technology and collaboration with parents.